Selective chemosensor phthalocyanines for Pd2+ ions; synthesis, characterization, quantum chemical calculation, photochemical and photophysical properties - Gunsel, Armagan; Kirbac, Erkan; Tuzun, Burak; Erdogmus, Ali; Bilgicli, Ahmet T.; Yarasir, M. Nilufer (ELSEVIER, 2019)
In this study, ligand (1) was prepared by a nucleophilic displacement reaction of (4-bromophenyl) methanethiol with 4-nitrophthalonitrile according to literature and its novel type peripheral substituted tetra phthalocyanines [CuPc (2), ZnPc (3) and GaPc (4)] were prepared. The phthalocyanines obtained from compound (1) were characterized by FT-IR, H-1 NMR, UV-Vis spectral data, elemental analysis, and MALDI-TOF. The novel phthalocyanines [CuPc (2), ZnPc (3) and GaPc (4)] were highly soluble in common organic solvents such as CHCl3, THF, CH2Cl2, DMSO and DMF. The effect of Pd2+ ions on the fluorescence emission and UV-Vis spectra were performed with addition of increasing amounts of Pd2+ ions. This functional phthalocyanines exhibited H-type aggregation versus Pd2+ ions due to special chemical structures, which can be used as a selective chemosensor for Pd2+ ions. Also, the molecular reactivity of the ligand (1) and related metallo phthalocyanines [CuPc (2), ZnPc (3) and GaPc (4)] were investigated and compared with the analysis of frontier molecular orbitals. In addition, photochemical and photo physical properties of these new phthalocyanines (fluorescence quantum yields, fluorescence behavior, singlet oxygen and photodegradation quantum yields) were studied in DMSO. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Metal sensor; Quantum chemical calculation; Photochemical; Photophysical; MOLECULAR-DYNAMICS SIMULATION; CORROSION-INHIBITORS DFT; THEORETICAL EVALUATION; SUBSTITUTED GALLIUM; SCHIFF-BASES; SOFT ACIDS; DERIVATIVES; FLUORESCENCE; INDIUM(III); COPPER(II); Chemistry